Secure and Efficient Query Processing Using Randomized Encryption and De-duplication on the Cloud - Lalita Kumar Parvataneni, Mohith; Sai Nath Adusumalli, Eswara; C, Rajeshbabu. (International Journal of Engineering and Technology, 2018)
Cloud computing [1] is the most upcoming area of the IT industry that helps the users to get rid of the hardware resources and complexity in storage and computational power. All the people started using cloud which led to many security concerns relating to the data confidentiality and integrity. This became a challenge to the widespread of the new cloud computing technology. Many measures are taken to improve the cloud security and then there came the concept of cryptography to upgrade the cloud security. Today, the main problem is to sustain data privacy [2] against unreliable cloud service providers and to provide correct query results to the authenticated users. Existing approach provide confidentiality using only one symmetric encryption algorithm which generates only one secret key to both encrypt and decrypt. But this is not so secured as the attacker can easily guess the algorithm and thereby find the key. In this journal, we proposed a randomized encryption technique in which the files are randomly encrypted by three strong algorithms AES, Triple DES and Blowfish [3] which improves the security and we are also implementing new techniques to improve security like key generation via OTP method, etc. In addition to this, we are also going to solve the storage issue of redundant or duplicate files consuming the cloud storage by using a file-level de-duplication technique which can eliminate the duplication of files uploaded into the cloud, thereby saving storage and reduce the need to buy extra storage.